Analisis Faktor-Faktor Ketimpangan Pendapatan di Pulau Jawa - Yozi Vionita; Artha, Dwirani Puspa (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research aims to determine the influence of the analysis of income inequality factors on the island of Java. This research uses secondary data sourced from the Central Statistics Agency (BPS). With research variables grouped into six parts, namely, the dependent variable uses income inequality with the Gini ratio indicator. The independent variables consist of education with an indicator of average years of schooling, the open unemployment rate with an indicator of the unemployment rate, economic growth with an indicator of the rate of economic growth, and the human development index with an indicator of the human development index. This research uses a panel data analysis method with the selected model being the Fixed Effect Model (FEM) with a cross section of 6 provinces on the island of Java in the 2014-2023 period. The results of this research show that education has a negative and significant relationship with income inequality (gini ratio). The open unemployment rate has a positive and significant relationship to income inequality (gini ratio). Population growth has a positive and significant relationship to income inequality (gini ratio). And the human development index has a positive and insignificant relationship with income inequality (gini ratio).